Improving chatter performance of a lathe spindle through grapho-optimization - Alzghoul, Mohammad; Sarka, Ferenc; Szabó, Ferenc János (Design of Machines and Structures, 2023)
Structural modifications to spindle systems have been demonstrated in previous studies to improve their dynamical performance. The aim of this study is to improve the performance of a lathe spindle system in terms of chatter occurrence, while maintaining the same overall mass of the system. The design of the spindle system is optimized using the grapho-optimization method, employing the Kuhn-Tucker optimality criterion to evaluate the design parameters. Specifically, the thickness of the spindle shaft and the diameter of the shaft next to the chuck are varied. The optimized spindle system shows a significant improvement in the first natural frequency value compared to the original design; the first natural frequency is increased by 59.7 %.